The Validity of Positive Coagulase-Negative Staphylococcus Cultures for the Diagnosis of Sepsis in the Neonatal Unit - Benenson, Shmuel; Cohen, Matan J.; Greenglick, Nofar; Schwartz, Carmela; Eventov-Friedman, Smadar; Ergaz, Zivanit (American Journal of Perinatology, 2022)
Objective Coagulase-negative Staphylococcus (CoNS) is the most frequent pathogen causing late-onset sepsis (LOS) in neonatal intensive care units (NICUs). Technical difficulties hinder blood culture (BC) collection and obtaining only one culture before initiating antibiotic therapy is a common practice. We sought to assess specific clinical information and CoNS cultures for the diagnosis of true bacteremia in the NICU.Study Design This historical cohort study was conducted in NICUs at the Hadassah-Hebrew University Medical Center of Jerusalem in Israel. Clinical and laboratory data in every CoNS bacteremia were collected and compared between bacteremia groups as follows: true positive, two positive BCs; contaminant, one positive BC out of two; undefined, one BC obtained and found positive.Results For 3.5 years, CoNS was isolated in 139 episodes. True positive was identified in 44 of 139 (31.7%), contaminant in 42 of 139 (30.2%), and the event was undefined in 53 of 139 (38.1%). Vancomycin treatment was more frequent in the true positive and undefined groups than the contaminant group (100, 90.6, and 73.8% respectively, p = 0.001); treatment was also prolonged in these two groups (p < 0.001). No clinical variables were associated with true bacteremia on multivariable analysis.Conclusion Diagnosis should definitely be based on at least two positive BCs, despite objective difficulties in obtaining BCs in neonates.Key Points
Keywords: coagulase-negative Staphylococcus; bacteremia; sepsis